You should isolate the variables such that:

`x(dy/dx)=3-y => (dx)/x = (dy)/(3-y)`

Integrating both sides yields:

`int (dy)/(3-y) = int (dx)/x`

You should use substitution to evaluate `int (dy)/(3-y)` such that:

`3-y = t => -dy = dt`

`int (dy)/(3-y) = int -(dt)/t = -ln|t| + c`

`int (dy)/(3-y) = -ln|3-y| + c`

`-ln|3-y| = ln|x| + c`

You need to find the constant c, hence, you need to substitute 1 for x and 1 for y in `-ln|3-y| = ln|x| + c` such that:

`-ln(3-1) = ln1 + c`

Since `ln 1 = 0 => c = -ln 2 = ln(1/2)`

`-ln|3-y| = ln|x| + ln(1/2) => ln(1/(3-y)) = ln|x| + ln(1/2)`

Using logarithmic identities yields:

`ln(1/(3-y)) = ln (x/2) => 1/(3-y) = x/2 => 2 = x(3-y)`

`2 = 3x - xy => 2 - 3x = -xy => y = (3x-2)/x`

**Hence, evaluating the solution to the given equation, under the given conditions, yields `y = (3x-2)/x` .**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now